Crohn's Disease Associated with Sweet's Syndrome and Sjögren's Syndrome Treated with Infliximab - Erina N. Foster; Khanh K. Nguyen; Rafiq A. Sheikh; Thomas P. Prindiville (Clinical and Developmental Immunology)
The association of Crohn's disease (CD) and Sweet's syndrome is rare and the presence of Sjögren's syndrome in Crohn's disease is even rarer, with only three reports found in the literature. We describe two cases of Crohn's disease associated with Sweet's syndrome, one of which is the first case of CD and Sweet's concomitantly associated with Sjögren's syndrome. Both cases responded rapidly to Infliximab therapy with complete resolution of the skin lesions.